Magnaporthe oryzae populations adapted to finger millet and rice exhibit distinctive patterns of genetic diversity, sexuality and host interaction - Takan, J.P.; Chipili, J.; Muthumeenakshi, S.; Talbot, N.J.; Manyasa, E.O.; Bandyopadhyay, Ranajit; Sere, Y.; Nutsugah, S.K.; Talhinhas, P.; Hossain, M.A.; Brown, A.; Sreenivasaprasad, S. (Springer, 2012)
In this study, host-specific forms of the blast pathogen Magnaporthe oryzae in sub-Saharan Africa (SSA) were characterised from distinct cropping locations using a combination of molecular and biological assays. Finger millet blast populations in East Africa revealed a continuous genetic variation pattern and lack of clonal lineages, with a wide range of haplotypes. M. oryzae populations lacked the grasshopper (grh) element (96%) and appeared distinct to those in Asia. An overall near equal distribution (47–53%) of the mating types MAT1-1 and MAT1-2, high fertility status (84–89%) and the dominance of hermaphrodites (64%) suggest a strong sexual reproductive potential. Differences in pathogen aggressiveness and lack of cultivar incompatibility suggest the importance of quantitative resistance. Rice blast populations in West Africa showed a typical lineage-based structure. Among the nine lineages identified, three comprised ~90% of the isolates. Skewed distribution of the mating types MAT1-1 (29%) and MAT1-2 (71%) was accompanied by low fertility. Clear differences in cultivar compatibility within and between lineages suggest R gene-mediated interactions. Distinctive patterns of genetic diversity, sexual reproductive potential and pathogenicity suggest adaptive divergence of host-specific forms of M. oryzae populations linked to crop domestication and agricultural intensification.